Combined assessment of Epstein–Barr virus viral capsid antigen and Epstein–Barr virus nuclear antigen‐1 serology for post‐transplant lymphoproliferative disorder risk stratification in adult solid organ transplant recipients. Issue 6 (6th September 2022) - Heldman, Madeleine R.; Edlefsen, Kerstin L.; Pepper, Gregory; Kapnadak, Siddhartha G.; Rakita, Robert M.; Fisher, Cynthia E.; Limaye, Ajit P.
Abstract: Background: Epstein–Barr virus (EBV) seronegative solid organ transplant recipients (SOTRs) are at increased risk for post‐transplant lymphoproliferative disorder (PTLD). Assays for EBV serostatus assess antibody to both EBV viral capsid antigen (VCA) and Epstein–Barr nuclear antigen‐1 (EBNA‐1), but PTLD risk among SOT recipients with discordant VCA and EBNA‐1 results is unknown. Methods: We performed a retrospective, single‐center cohort study to determine the risk of PTLD among adult (≥ 18 years) SOTRs with discordant pre‐transplant VCA and EBNA‐1 IgG compared to that of SOTRs with concordantly negative or concordantly positive serology using univariable and multivariable Cox‐proportional hazards models. Results: Of 4106 SOTRs, the number (%) who were concordantly positive, concordantly negative, and discordant was 3787 (92.2%), 149 (3.6%), and 170 (4.2%), respectively. The adjusted hazard of PTLD was significantly higher among discordant SOTRs compared to concordantly positive SOTRs (aHR 2.6, 95% CI 1.04–6.6, p =.04) and lower compared to concordantly negative SOTRs (aHR 0.27, 95% CI 0.10–0.76, p <.001). The adjusted hazard of EBV+ PTLD among those with discordant serology was also significantly higher compared to the concordantly positive cohort (aHR 3.53, 95% CI 1.04–12.0, p =.04) and significantly lower compared to the concordantly negative cohort (aHR 0.23, 95% CI 0.06–0.82, p =.02). Conclusions: Risk of PTLD among SOTRs with discordant VCA and EBNA‐1 may be intermediate between those with concordantly positive and negative serology. If confirmed in future studies, revision of national EBV serology reporting to include both VCA and EBNA results may be needed to optimize PTLD risk stratification. Abstract : Graphical abstract: